Machining metal matrix composites: novel analytical force model. Issue 1 (March 2016) - Ghandehariun, A.; Hussein, H.; Kishawy, H.
Abstract Outstanding mechanical characteristics make metal matrix composites (MMCs) applicable to many industrial applications. However, the very hard reinforcements that provide such remarkable features for MMCs also cause challenges during the machining process. This paper tries to address these challenges through development of a novel analytical model for prediction of cutting force during machining these composites. The force model is based on calculation of power consumption in different parts of the cutting system. The model considers the plastic deformations, different types of friction at various interfaces and debonding and fracture of reinforcements. The cutting force values predicted by the model are compared with experimental values for various MMCs at different cutting conditions. The close agreement between the results verifies the ability of the model to provide accurate estimation of the cutting force during machining MMCs.